Стан і перспективи оптимізації трав’янистої рослинності дендропарку “Тростянець” - Nesterenko, V.P.; Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The analysis of the condition of grassy phytocenosic of the park, including the phytocenotic characteristics, degree of synantropization, decorative potential and direction of alterations were done. The way of the improvement of grassy vegetation was designed.